Hydrology days award - Pinder, George F., author; Colorado State University, author; Colorado State University, publisher (Colorado State University. Libraries, 2009)
The 2009 Hydrology Days Award was presented to George F. Pinder. Included is the abstract for his award lecture "Optimal search strategy for the definition of a dense non-aqueous phase liquid (DNAPL) source" given on March 26, 2009.
Hydrology days 2009
AGU hydrology days 2009
2009 annual AGU hydrology days was held at Colorado State University on March 25 - March 27, 2009.
Keywords: Hydrology -- Congresses; Award winners